Land Use and Port-city Integration in Reclamation Areas: A Comparison between Spain and Japan - Martín-Antón, Mario; del Campo, José María; Negro, Vicente; Frades, Jorge Luengo; Moreno Blasco, Luis J.; Jiménez Verdejo, Juan Ramón (Journal of Coastal Research, 2020)
Martín-Antón, M.; del Campo, J.M.; Negro, V.; Luengo Frades, J.; Moreno Blasco, L.J., and Jiménez Verdejo, J.R., 2020. Land use and port-city integration in reclamation areas: A comparison between Spain and Japan. In: Malvárez, G. and Navas, F. (eds.), Global Coastal Issues of 2020. Journal of Coastal Research, Special Issue No. 95, pp. 278–282. Coconut Creek (Florida), ISSN 0749-0208. Land reclamation is an increasingly widespread practice, especially in Asia in recent years as a means to provide land above sea level in cities with land shortage. This is the case of Japan, especially in the populated bays of the south coast (Tokyo, Nagoya, Osaka-Kobe). After a worldwide research on this subject (Martín-Antón et al., 2016), a more specific study of the reclaimed areas in Spain and Japan, with their respective land uses, is made in this work to show the needs of growth of the port cities of each country. Two representative bays have been analyzed in detail, namely Algeciras-Gibraltar Bay in Spain and Osaka-Kobe Bay in Japan. The Algeciras Bay has a total reclaimed area of 5.6 km2 whereas Osaka Bay has almost 160 km2 built over the centuries. In the latter, a large percentage of the new land is currently dedicated to residential use (17%), about 28 km2. Much of the housing land is next to, or even surrounded by, industrial zones, which add up to more than 60 km2 (almost 40%), compared to 24% in Algeciras. In Gibraltar (Algeciras Bay), the reclaimed area with residential use is 0.5 km2. It is remarkable the land areas in disuse: 8% of the total in Osaka Bay and 22% in Algeciras Bay. However, more and more land reclamation works are being built, including unfilled water areas surrounded by breakwaters (some of them to be filled with solid waste), such as the 2.6 km2 in Osaka Bay. Another use is energy production, with 0.6% of the total reclaimed area in Osaka Bay dedicated to solar power plants (0.89 km2). This article aims to make a reflection on current urban needs in port areas, port-city integration and the impact on the landscape of large maritime works.